Laparoscopic Resection of a Gastric Plasma Cell Granuloma: A Case Report - Christopher Horn; Huw G. Jones; Gareth Leopold; Anna Mainwaring; Ashraf Rasheed (Case Reports in Pathology)
Plasma cell granuloma, also known as inflammatory myofibroblastic tumour or inflammatory pseudotumour, is a nonneoplastic process characterized by an unregulated growth of inflammatory cells. It most commonly occurs in the lung and upper respiratory tract, and only six other cases of gastric plasma cell granuloma exist. There are no other cases of intragastric laparoscopic resection of this type of lesion. Here, we present a case of a 60-year-old gentleman who had gradual onset epigastric discomfort and was thought to have a gastrointestinal stromal tumour on gastroscopy. Subsequent imaging and laparoscopic transgastric resection of the lesion confirmed the presence of a plasma cell granuloma. We discuss the aetiologies, presentation, investigation, and treatment of this rare disorder and make recommendations on the management.